Designing one nation the politics of economic culture and trade in divided Germany - Schreiter, Katrin (Oxford scholarship online, 2020)
The histories of East and West Germany traditionally emphasize the Cold War rivalries between the communist and capitalist nations. Yet, even as the countries diverged in their political directions, they had to create new ways of working together economically. This text examines the material culture of increasing economic contacts in divided Germany from the 1940s until the 1990s